2022
DOI: 10.7166/33-3-2810
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Reclamation of Waste Sand Produced by Additive Manufacturing Processes

Abstract: Metal casting manufacturers are increasingly adopting three-dimensional printing in their workflows as a way to remain competitive. Despite all the innovative development, strict environmental regulations and the intrinsic value of sand still make the recycling of waste sand an essential matter to consider when implementing the rapid sand-casting process. During the printing of the furan-bonded sand cores using binder jetting processes, waste sand is produced. This paper investigates the possibility of mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A previous study was conducted to characterise the waste sand generated during threedimensional printing (3DP) on a Voxeljet printer, which included properties such as size distribution, grain shape, loss on ignition (LOI), and pH [12]. The pH results confirmed the presence of residual sulphonic acid and furfuryl alcohol resin in the used sand obtained from the 3DP process after printing.…”
Section: Precoatermentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study was conducted to characterise the waste sand generated during threedimensional printing (3DP) on a Voxeljet printer, which included properties such as size distribution, grain shape, loss on ignition (LOI), and pH [12]. The pH results confirmed the presence of residual sulphonic acid and furfuryl alcohol resin in the used sand obtained from the 3DP process after printing.…”
Section: Precoatermentioning
confidence: 94%
“…Figure 11 and Figure 12 for all three sands reclamation were over the minimum requirement of 200 N/cm 2 therefore all three reclamation methods can be considered effective. According to the study conducted by Motlhabane et al (2022) [18] results showed that mechanical reclamation by dry attrition the tensile strength could achieve the minimum requirement of 220 N/cm 2 . Used sand 2 was above the minimum tensile strength requirement for all the reclamation methods.…”
Section: Tensile and Bend Strengthsmentioning
confidence: 99%
“…The binder jet printing is best explained by Figure 1 below. [4] After printing the sand moulds and cores, any loose sand is carefully removed and disposed of or could be recycled and reclaimed [5]. The reclamation processes are normally mechanical and thermal reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which the sand has been heated directly correlates with the efficiency of the sand reclamation process and up to 90% of reclaimed sand may be used. Motlhabane et al [5] have studied the mechanical reclamation of the wasted sand generated by the 3D Printing. It was found that it could produce renewed sand complying with the specification of the Original Equipment Manufacturer, which is the Voxeljet VX1000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation